An 18-week model of Parent–Child Interaction Therapy: clinical approaches, treatment formats, and predictors of success for predominantly minoritized families - Jent, Jason F.; Rothenberg, William A.; Peskin, Abigail; Acosta, Juliana; Weinstein, Allison; Concepcion, Raquel; Dale, Chelsea; Bonatakis, Jessica; Sobalvarro, Cindy; Chavez, Felipa; Hernandez, Noelia; Davis, Eileen; et al. (Frontiers in Psychology, 2023)
Disruptive behavior disorders are among the most prevalent pediatric mental health referrals for young children. However, families from historically minoritized social identities have experienced disparities in treatment access, retention, and outcomes. Evidence-based interventions such as Parent-Child Interaction Therapy (PCIT) have been found to be effective in reducing children's disruptive behaviors in minoritized families. However, variable treatment length as a result of skill-based graduation criteria (e.g., observed caregiver verbalizations) may slow and/or hinder treatment progress, particularly for families where expected treatment verbalizations are less linguistically relative (e.g., no exact English to Spanish translations) and/or culturally familiar. Time-limited PCIT has been proposed as a strategy for promoting equity in treatment completion and outcomes amongst minoritized families, because treatment progression and/or completion is not contingent upon caregiver linguistic skill demonstration. The current study evaluated the overall effectiveness of an 18-week model of PCIT and examined predictors of retention and treatment outcomes. Participants (N= 488 dyads) included predominantly racially, ethnically, linguistically, and socioeconomically diverse children aged two to eight years, and their caregivers. Overall findings indicate that the 18-week PCIT model is an effective intervention for reducing children's externalizing and internalizing behaviors and improving caregiver parenting skills for most treatment completers. Despite advances in treatment completion, some caregiver social identities and PCIT treatment characteristics were predictive of lower completion rates and/or less optimal treatment outcomes. Overall, this study provides strong support for widely disseminating use of the 18-week model of PCIT for most families served. Clinical implications and considerations for continued treatment inequity are discussed.